Розвиток моделі визначення коефіцієнтів втрат об'ємного аксіально-поршневого гідравлічного приводу - Трембач, Олексій Сергійович; Кожушко, Андрій Павлович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Дана стаття має за мету надати рекомендації щодо уточнення значень коефіцієнтів об’ємних втрат в гідрооб’ємній передачі за рахунок використання математичної моделі визначення об’ємного ККД та методу оптимізації для знаходження оптимального значення цільової функції. При вирішенні поставленої мети використовувалась методика, яка складається з пошуку оптимального значення коефіцієнтів об’ємних втрат при використання методу оптимізації з лінійною цільовою функцією та зіставленні теоретичного результату з експериментальними даними. Практична значимість роботи полягає у технічно-обґрунтованому виборі значень коефіцієнтів об’ємних витрат регульованого гідронасосу та нерегульованого гідромотору, що підвищує точність обчислення ефективності гідрооб’ємної передачі.

In recent decades, agricultural vehicles equipped with a power transmission unit consisting of a hydraulic drive have become widely used. Thus, in agricultural tractors, the hydraulic drive implements one of the energy flows in the hydraulicmechanical transmission. Axial-piston hydraulic machines, which can be controlled or uncontrolled, are introduced in such means. During the operation of agricultural tractors with hydraulic-mechanical transmissions, a wide range of dynamic loads is applied to the hydraulic transmission, which causes the appearance of jump-like values of torque and angular velocity. This leads to a more accurate determination of energy losses in the hydro-displacement drive. Therefore, the material of this article is aimed at providing recommendations for specifying the values of the volumetric loss coefficients in the hydro-displacement transmission, using a mathematical model for determining the volumetric efficiency and an optimization method for finding the optimal value of the objective function. In solving the set objective, a technique was used that consists of finding the optimal value of volumetric loss coefficients using the optimization method with a linear objective function and comparing the theoretical result with experimental data. As a result, scientifically based recommendations for the selection of volume loss coefficients in a regulated hydraulic pump and an unregulated hydraulic motor, which have nonlinear dependencies, are provided. The practical significance of the work lies in the technically justified choice of the values of the coefficients of volumetric losses of the regulated hydraulic pump and the unregulated hydraulic motor, which increases the accuracy of the calculation of the efficiency of the hydrostatic transmission.
Development a model for the determination the loss coefficients of volume axial piston hydraulic drives
Keywords: гідрооб'ємна передача; гідронасос; гідромотор; ККД; оптимізація; коефіцієнти об'ємних втрат; hydrostatic transmission; hydraulic pump; hydraulic motor; efficiency; optimization; volumetric loss coefficient